Penguatan Moderasi Beragama Sejak Dini di Kalangan Siswa untuk Menjaga Toleransi dan Mencegah Konflik Sosial Keagamaan - Dessi Puspita Rani; Eka Rifna Fauziah; Risa Maya Putri; Nanda Ridwan Setiyaji (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: Strengthening religious moderation from elementary school is crucial for maintaining tolerance and preventing potential socio-religious conflicts. SDN 02 Bedono is a relevant context for examining how the values of moderation are instilled in upper-grade students. Objective: To analyze the form, process, and effectiveness of strengthening religious moderation in upper-grade students at SDN 02 Bedono as an effort to maintain tolerance and prevent socio-religious conflicts. Method: Qualitative research with a case study design. Data were collected through interviews and observations of learning practices and school culture, and then analyzed thematically to identify patterns of strengthening moderation values. Results: Students demonstrated a practical understanding of religious moderation that was internalized in their daily behavior. The reinforcement of values took place through a combination of formal approaches (learning activities and school programs) and habituation, with teachers playing the role of moral and social role models. Conclusion: Elementary schools hold a strategic position in shaping tolerant character; at SDN 02 Bedono, religious moderation has become an integral part of the school's social norms, as reflected in the interactions between students. Contribution: This study presents a model of good practice for strengthening religious moderation at the elementary school level, which can be replicated or adapted by other educational institutions to instill national values and promote harmony from an early age.